The pursuit of political will: decision makers' incentives and gender policy implementation in the Western Balkans. Issue 2 (3rd April 2018) - Spehar, Andrea
ABSTRACT: In the Western Balkans, just as in newly democratized countries in other regions, failures in gender policy implementation are often attributed to lack of "political will." There is however a surprising lack of specificity concerning what is meant by it and how to measure its influence on the observed implementation gaps. To help to begin filling this research gap this article examines the extent to which Western Balkans countries might be failing in the implementation of their adopted gender policies and the reasons why decision makers seem to lack the political will to implement them. To allow for a more in-depth perspective, the analysis will concentrate on the case of the implementation of Gender Responsive Budgeting (GRB) on the municipal level in the three countries in its focus: Bosnia and Hercegovina; Macedonia; and Serbia. The empirical material used for it consists of primary data from telephone surveys, in-depth interviews with actors involved in GRB policy processes and official documents.